PENGARUH PENERAPAN ISO 9001:2008 TERHADAP PENINGKATAN KINERJA KERJA KARYAWAN PT. SOFTEX INDONESIA - Ade Irpan Sabilah; Hernadewita Hernadewita; Sadiq Ardo Wibowo; Yan Mahesa Damanik; Elva Susanti (JURNAL REKAYASA SISTEM INDUSTRI, 2019)
Quality management system is the ability of an organization to maintain the quality of goods or services that are served. The efforts made by the company are to improve the management system that is prime with ISO 9001: 2008 which is an international requirement for a company's management system. PT Softex Indonesia is the first producer of sanitary napkin made in Indonesia which has obtained ISO 9001: 2008 certificate and applied it in the implementation of production activities. One way to achieve success in maintaining the quality of a product is by improving work performance in order to produce quality products. Based on this, the researchers analyzed the effect of implementing ISO 9001: 2008 on improving employee performance. The data used in this study were obtained from a questionnaire (primary) and several observations and direct interviews with parties related to employee performance. The analysis technique used is simple regression using hypothesis testing, namely F test and t test. Based on the results of the study the magnitude of the influence of the application of ISO 9001: 2008 which directly affects the improvement of employee performance. From this study, R Square value was 0.504, which means that 50.4% of employee performance improvement variables can be explained by its independent variables, namely ISO 9001: 2008, while the remaining 49.3% is explained by other variables outside of this study.